Ring chromosome 7 in a child with T-cell acute lymphoblastic leukemia with myeloid markers. Issue 2 (4th March 2021) - Tirado, Carlos A.; Reyes, Andrew; Yeh, Wilson; Yee, Justin; King, Joy; Kane, Javier; Koss, William
Abstract: Ring chromosomes are uncommon in hematological diseases. Here we present the case of a 13-year-old girl with leukocytosis, anemia, and lymphadenopathy. Flow cytometry analysis revealed a predominant precursor T lymphoid population expressing CD7, CD5, CD2, and cytoplasmic CD3 with partial expression of CD33, CD34, CD117, and CD11c; TdT was positive, and myeloperoxidase was negative. The bone marrow aspirate showed markedly increased blasts that were positive for CD3, CD7, CD34, TdT, and myeloperoxidase (rare positivity) by immunohistochemistry stain, consistent with T-cell acute lymphoblastic leukemia (T-ALL) extensively involving a hypercellular marrow for age. The karyotype showed a ring 7 in 12 of the 21 metaphase cells examined and deletions of the subtelomeric regions on chromosome 7. Deletions in the short arm of chromosome 7 and the long arm of chromosome 7 are present in 2% to 4% of pediatric T-ALL cases. Ring chromosome 7 is typically seen in myeloid malignancies, including acute myeloid leukemia.